Identification of a novel splicing mutation in the SLC25A13 gene from a patient with NICCD: a case report - Linlin Zhang; Yingying Li; Wenli Shi; Jinshuang Gao; Yuan Tian; Ying Li; Yaqing Guo; Shihong Cui; Xiaoan Zhang (BMC, 2019)
Abstract Background Neonatal intrahepatic cholestasis caused by citrin deficiency (NICCD) is an autosomal recessive disorder and one of the most common inherent causes of cholestatic jaundice in Asian infants. Mutations in the SLC25A13 gene, which encodes citrin protein expressed in the liver, have been identified as the genetic cause for NICCD. Case presentation Here, we report a 4-month-old female with clinical features including jaundice, hyperbilirubinemia, hyperlactacidemia, and abnormal liver function. The patient was diagnosed with NICCD by differential diagnosis using genetic analysis. Mutations in 60 jaundice-related genes were tested by using amplicon sequencing, which was performed on an Ion S5XL genetic analyzer. A compound heterozygous mutation in the SLC25A13 gene was identified, consisting of a known deletion SLC25A13:c.852_855delTATG and a novel splicing mutation SLC25A13:c.1841 + 3_1841 + 4delAA. Sanger sequencing for the proband and her parents was performed to validate the result and reveal the source of mutations. Conclusion A compound heterozygous mutation in the SLC25A13 gene was identified in a 4-month-old female patient with NICCD. Our data suggest that amplicon sequencing is a helpful tool for the differential diagnosis of inherited diseases with similar symptoms. Further studies of the mutation spectrum of neonatal jaundice in China are warranted.